Ridhaa in Islamic Marriage Law: Reconstructing Consent under Psychological Coercion - Alfiandri; Abraham Zakky Zulhazmi; Akhmad Nizaruddin; Faiz Husaini; Ahmad Irfan (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This article reconstructs the concept of ridhaa (marital consent) in Islamic marriage law by incorporating psychological coercion as a form of defective consent that remains under-theorized in contemporary fiqh discourse. While classical doctrines of ikrah primarily focus on physical coercion and explicit threats, recent interdisciplinary studies in psychology have demonstrated that coercive control operates through non-physical mechanisms such as emotional manipulation, dependency, and behavioral domination, significantly impairing autonomous decision-making. This study employs a qualitative-normative approach grounded in ushul al-fiqh and maqashid al-shari'ah, supported by a systematic engagement with multi-madhhab fiqh sources and contemporary psychological literature on coercive control. By adopting a functional interpretation of ikrah, the analysis examines whether psychological coercion fulfills the same legal rationale ('illah) as classical coercion in invalidating consent. The findings argue that ridhaa should be conceptualized not merely as formal agreement but as substantively free will, protected from structural domination. Psychological coercion can therefore be framed as dhaarar nafsi that undermines legal agency and qualifies as a defect of consent within an ushulī framework. This study contributes by offering a more precise maqashid-based reconstruction of consent that bridges classical fiqh doctrine and contemporary empirical insights, while also identifying doctrinal limits to prevent over-expansion of ikrah.